Practical applications and learning curve for EUS-guided hepaticoenterostomy: results of a large single-center US retrospective analysis - James, Theodore W.; Baron, Todd H. (Endoscopy International Open, 2019)
Background and study aims Endoscopic ultrasound-guided hepaticoenterostomy (EUS-HE) is an effective method of endoscopic biliary drainage in cases where endoscopic retrograde cholangiopancreatography has failed or is deemed impossible. Indications for EUS-HE have expanded, resulting in increased interest by endoscopists to learn the procedure; however, few data exist on breadth of application or experience needed to develop proficiency. We describe utilization of EUS-HE for biliary decompression at a large tertiary referral center along with procedural learning curve.Patients and methods Retrospective evaluation of 60 consecutive patients who underwent attempted EUS-HE by one endoscopist from February 2016 through June 2018. Procedures were divided into chronological and summative experience quartiles. We compared procedural success rate, procedural utilization, and procedure duration over time. Results Sixty patients underwent attempted EUS-HE during the study period: 35 with surgically altered anatomy, 23 with malignant biliary obstruction, 35 outpatients, 35 females; median age, 66 years. The procedure was technically successful in 53 patients. Success rates by summative experience quartile were 80 %, 80 %, 93.3 % and 100 % respectively. Beginning at patient number 40, the remaining cases had a success rate of 100 %. Utilization increased from eight cases in the first chronological quartile to 28 in the fourth. There was no significant reduction in procedure duration over time. Conclusion For an experienced endoscopist, EUS-HE could be performed effectively and safely after the experience of 40 cases. Limitations of this study include a single endoscopist and heterogeneous patient population with variable anatomy that may affect procedural success. Future studies should include data from multiple centers and endoscopists.